Cardiovascular risk factor associations in adults with psychosis and adults in a national comparator sample. (August 2015) - Foley, Debra L; Mackinnon, Andrew; Morgan, Vera A; Watts, Gerald F; Shaw, Jonathan E; Magliano, Dianna J; Castle, David J; McGrath, John J; Waterreus, Anna; Galletly, Cherrie A
Objective: Antipsychotic drug treatment alters status on key risk factors for cardiovascular disease. The aim of this study was to test whether cardiovascular risk factor associations differ in adults with psychosis and adults from the general community. Method: Data were analysed for those aged 25–64 years from a nationally representative psychosis sample ( n = 1, 457) and a national comparator sample ( n = 8, 866). The Pearson correlation coefficient was used to estimate the association among tobacco use, body mass index, waist circumference, diastolic and systolic blood pressure and fasting total-, LDL- and HDL-cholesterol, triglycerides and plasma glucose. The robust Levene test was used to test for sample differences in variance. Results: Correlations among cardiovascular risk indicators and between cardiovascular risk indicators and age were often significantly weaker in those with psychosis than in those from the national comparator sample. This was not due to a reduction in variance within the psychosis sample. Conclusions: Risk prediction that synthesizes multivariate risk indicator data needs to be connected to verified cardiovascular morbidity and mortality in those with psychosis to determine if standard risk calculators adequately discriminate those at high, medium and low future risk of cardiovascular morbidity and mortality. Until then the clinical implications of low or absent correlations among cardiovascular risk indicators and their low or absent association with increasing age is unclear but may indicate that risk equations commonly used in the general population may not be applicable for those with treated psychosis.